The use of near infrared reflectance spectroscopy to study chemical changes in the leaf litter consumed by saprophagous invertebrates (SOIL BIOLOGY & BIOCHEMISTRY, 2001)
Chemical changes in holm oak leaf litter that was consumed by the millipede Glomeris marginata were studied using near infrared reflectance spectroscopy. Compared to leaf litter, faecal pellets were significantly richer in lignin and poorer in nitrogen and readily assimilable constituents. The C:N ratio was significantly higher in the faeces. A NIRS-predicted index of litter decomposability was found to be lower in the faeces than in uneaten litter. (C) 2001 Elsevier Science Ltd. All rights reserved.